The effect of habitats and fitness on species coexistence in systems with cyclic dominance. (7th February 2020) - Baker, Ryan; Pleimling, Michel
Highlights: Extensive numerical simulations of systems with cyclic dominance composed of three and six species are performed. Structured spatial heterogeneities in form of habitats that locally provide one species with an advantage are found to destabilize spiral waves. Species extinction probabilities display a succession of maxima as function of time. A transition between stable coexistence and unstable coexistence takes place. Inclusion of species fitness has a quantitative effect and delays species extinction. Abstract: Cyclic dominance between species may yield spiral waves that are known to provide a mechanism enabling persistent species coexistence. This observation holds true even in presence of spatial heterogeneity in the form of quenched disorder. In this work we study the effects on spatio-temporal patterns and species coexistence of structured spatial heterogeneity in the form of habitats that locally provide one of the species with an advantage. Performing extensive numerical simulations of systems with three and six species we show that these structured habitats destabilize spiral waves. Analyzing extinction events, we find that species extinction probabilities display a succession of maxima as function of time, that indicate a periodically enhanced probability for species extinction. Analysis of the mean extinction time reveals that as a function of the parameter governing the advantage of one of the species a transition between stable coexistence and unstable coexistence takes place. We also investigate how efficiency as a predator or a prey affects species coexistence.